Information Risk Management A practitioner's guide - Sutton, David (BCS, The Chartered Institute for IT, 2021)
Information risk management (IRM) is about identifying, assessing, prioritising and treating risks to keep information secure and available. This accessible book is a practical guide to understanding the principles of IRM and developing a strategic approach to an IRM programme. It is the only textbook for the BCS Practitioner Certificate in Information Risk Management and this new edition reflects recent changes to the syllabus and to the wider discipline.